Ecosystem services research in Portugal - Campos, Felipe (2019)
Campos, F., David, J., & Cabral, P. (2019). Ecosystem services research in Portugal: are we on the right track. 192. Abstract from 15th European Ecological Federation (EEF) Congress and 18th National SPECO Meeting, Lisboa, Portugal.